MODERN DIGITAL SOLUTIONS IN MEDICAL TRAINING: EXPERIENCE, CHALLENGES, AND TRENDS - Shukurov Lazizbek Elbek ugli (Bright Mind Publishing, 2025)
Modern medical education is rapidly transforming under the influence of information technologies (IT). This article explores the main directions of IT application in the training of medical professionals, including e-learning, simulation technologies, virtual and augmented reality, and telemedicine. Special attention is given to analyzing the effectiveness of digital tools in developing clinical and cognitive competencies of future doctors. The paper provides an overview of both international and domestic experiences, identifying key trends and challenges in the digitalization of medical education.
Keywords: Telemedicine, educational resources, virtual simulators, animations, multimedia materials, online courses, virtual practice.